Insects and mites feeding on berries of Juniperus foetidissima Willd. on the Mediterranean island of Cyprus - Moraiti, Cleopatra A.; Kadis, Costas; Papayiannis, Lambros C.; Stavrinides, Menelaos (My University, 2019)
Endemic forests with Juniperus spp. in the Mediterranean are listed as a priority habitat in the EU Habitats Directive, with the stinking juniper tree (Juniperus foetidissima Willd.) a key constituent. Within the EU, the island of Cyprus represents the southernmost range of distribution of J. foetidissima with clumps of the tree located mostly on the rocky and steep slopes of the Troodos National Forest Park (NFP) between 1.500–1.950 m above sea level. The reproductive potential of J. foetidissima may be at risk, partly because of berry attacks by arthropods. To identify the arthropod species that infest J. foetidissima berries we sampled trees biweekly for one year at three elevations (1.950 m, 1.800 m, and 1.650 m). We identified four microlepidoptera species attacking berries: Pammene mariana (Zerny), P. juniperana (Millière), P. blockiana (Herrich-Schäffer) (Lepidoptera: Torticidae) and Argyresthia aurulentella Stainton (Lepidoptera: Yponomeutidae). Eriophyid mites were also recorded to feed on berries. All insect species are recorded for the first time in Cyprus. Infestation during the maturation period of berries collected by cutting varied from an average of 16% at the medium elevation (1.800 m) to 11% at the low elevation (1.650 m). Infestation of berries collected by beating remained above 30% during the berry maturation period.
Keywords: Seed predators; Arthropods; Pre-dispersal seed predation; EU priority habitat